Rapport Basic Soul - Zerbo, Armel (Fluid Ontologies of Contestation. Social media, anti-government protest and transnational decolonization movements in Burkina Faso, 2023)
The document offers an analysis of Internet users' comments relating to the publications of Souleymane Ouédraogo alias Basic Soul over the period from October 25 to 31, 2014.
Keywords: Social media; Decolonisation; Basic Soul; Manifestant; Protester; Right to Resist